Implementasi Model Pembelajaran Kooperatif Tipe Numbered Head Together Untuk Meningkatkan Kemampuan Kolaborasi Matematis Siswa Kelas VII SMP Santa Lusia Sei Rotan - Elpita Cyndi Claudia Simarmata; Ribka Kariani Sembiring; Imelda (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to find out whether the implementation of the Numbered Head Together type cooperative learning model can improve students' mathematical collaboration abilities in class VII of Santa Lusia Sei Rotan Middle School. This research method uses Classroom Action Research (PTK). The research procedure is cyclical. Each cycle consists of 4 stages, namely: planning, implementing actions, observing and reflecting. Data collection techniques through observation and tests. This data collection uses several instruments in the form of teacher observation sheets and student observation sheets. Meanwhile, to determine students' mathematical collaboration abilities, tests are used. The results of the research show that the use of the Numbered Head Together type cooperative learning model can improve students' mathematical collaboration abilities in mathematics lessons on algebra material. From the average value of the prerequisite abilities, namely 46, the average value of the mathematical collaboration ability of students in cycle I is 71 and the average value of the mathematical collaboration ability of students in cycle II is 76 and the teacher and student activity scores in cycle I are 64% and 59%. , and cycle II, namely 83% and 84%.